Engineering fundamentals an introduction to engineering - Moaveni, Saeed (Thomson, 2005)
Motivating students from all engineering disciplines, this text encourages students to become engineers and prepares them with a solid foundation in fundamental principles and physical laws. The book begins by introducing students to the exciting world of engineering as they discover what engineers do as well as the various areas of specialization. After explaining good study habits and what it takes to succeed, Moaveni then prepares them for success with an introduction to design and problem solving, communication, and ethics. Once this foundation is established, the book moves on to the basic physical concepts and laws students will encounter regularly as engineering students. The text emphasizes that engineers apply physical and chemical laws and principles as well as mathematics to design, test, and supervise the production of millions of parts, products, and services that people use everyday. By gaining problem solving skills and an understanding of fundamental principles, students are on their way to becoming analytical, detail-oriented, and creative engineers.